Relationship between Mindfulness and Meta-Emotion on Predicting Emotional Adjustment of Novice Nurses - K Babaei Nadinluye; F Mikaeli Manee; H Pezeshki; H Bafande; H Abdi (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: New graduate nurses suffer high levels of stress which can lead to unpleasant personal and professional outcomes. The aim of this study was to investigate the role of mindfulness and meta-emotion on predicting Emotional Adjustment in novice nurses. Material & Method: The descriptive-correlative method was used for conducting this research. The Statistical population was consisted of all the nurses in Tabriz. A sample of 120 subjects (60 females and 60 males) was randomly selected, using multistage random cluster. For data collection, Cognitive Emotion Regulation Questionnaire (CERQ), Mindfulness Questionnaire and Meta-emotion Questionnaire was used. The data gathered were analyzed by Pearson correlation and multiple regression, using simultaneous enter method. The data were analyzed by SPSS statistical software (version 21). Results: The Finding indicated that there was a positive relationship between mindfulness and meta-emotion (P<0/01) and between positive Emotional Adjustment and there was a negative relationship between meta- emotion (P<0/01) and negative emotional- cognitive regulation and mindfulness (P<0/01). The results showed that through using the scores from mindfulness and meta-emotion components of novice nurses, we can predict the rate of Emotional Adjustment (P< 0/01). Conclusion: According to the results, novice nurse's cognitive emotion regulation can be improved by teaching mindfulness and meta-emotion skills, and through awareness of the emotions, they can use them efficiently and improve their performance.